Analysis of Bawaslu's Authority as a Supervisory Institution in Resolving Election Disputes - Manihuruk, Teresa Akgriana Putri; Sinaga, Budiman (Manunggal Halim Jaya, 2025)
In enforcing Pilkada violations, the Election Supervisory Agency (Bawaslu) has the authority to supervise and resolve disputes over the electoral and regional election processes. This has been stated in the legislation that Bawaslu is authorized to deal with structured, systematic, and mass administrative violations in the application of law in Indonesia. In its settlement in the Constitutional Court also holds ownership of this authority with regard to disputes over election results that should be able to achieve legal certainty. In Law Number. 7 of 2017 concerning General Election Regulations, Bawaslu's role in monitoring and eradicating money politics is not ideal because it has obstacles that prevent and punish money politics in regional head elections. Bawaslu needs to continue to develop its human resources. The purpose of Bawaslu's establishment is to increase effectiveness as an election supervisory body and supervise the recruitment budget to create honest, fair and election results.